Cultural Tourism: A Strategy to Improve the Tourism Industry and Preserve Indonesian Culture - Agus Sunatha Putra; Gusti Made Riko Hendrajana; Komang Shanty Muni Parwati; Komang Trigita Juliastari; Firlie Lanovia Amir (Yayasan Inovasi Kemajuan Intelektual, 2025)
Cultural tourism has become a strategic pillar in national economic development and a vital instrument in preserving Indonesia's cultural heritage. This study aims to analyze the effectiveness of cultural tourism as a dual strategy to strengthen the competitiveness of the tourism industry and ensure the sustainability of cultural heritage amidst globalization. Using a descriptive qualitative approach, this article examines the synergy between local wisdom-based destination promotion and traditional value conservation efforts. The analysis shows that cultural integration in the tourism industry not only increases the volume of international and domestic tourist visits but also creates a collective awareness of local communities' cultural identity. However, challenges such as cultural commodification and the destruction of physical artifacts require tourism management policies based on sustainability principles. This article concludes that synchronization between stakeholders, digital innovation, and local community involvement is key to achieving a balance between industry profitability and the protection of Indonesian culture.